THE NEED TO USE CONTRASTIVE ANALYSIS FOR ELT IN ISLAMIC HIGHER EDUCATION INSTITUTIONS - Shahibul Muttaqien Al-Manduriy (OKARA: Jurnal Bahasa dan Sastra, 2018)
The teaching of English in Islamic Higher Education Institutions must be integrated by Islamic values. Since, it is very important for every teacher and lecturer in Islamic Educational Institutions from very early beginning to integrate Islamic values in terms of internalizing those values in the materials taught in the process of teaching and learning. Contrastive analysis is an approach to determine the similarities and differences between two languages. This approach is appropriate to be used in Islamic Higher Education Institutions, since the majority of the students in these Institutions are from Islamic Boarding Schools who had already learned Arabic as their basis of L2. This will help the lecturers to use contrastive analysis between Arabic and English in their English teaching. Considering that their consciousness about Language will help them to learn another language. It is also as one of the integration of Islamic values in English Language Teaching in Islamic Higher Education Institutions, because Arabic is one of cultural values of Islam.